Elastic Characteristics of Digital Cores from Longmaxi Shale Using Lattice Spring Models (Communications in Computational Physics, 2020)
Effective medium methods for the attribution of micro-structures to macroelastic properties of shales are important for the prediction of sweet spots in the shale-gas production. With X-ray micro-computed tomography (XMCT), the micro-structuresof shale core samples from Longmaxi Formation are visualized and characterized by3D digital images. As an efficient alternative to conventional effective medium methods for estimating elastic properties, we propose a consistent workflow of lattice springmodeling (LSM) to emulate the digital cores using three types of lattices. Particularattention is paid to investigate the effective Young's moduli, Poisson's ratios, and preferred orientations, by uniaxial compression tests along two directions. Within elasticdeformation, the impact of lattice arrangements on the anisotropy is even more thanthose of stress disturbances and micro-structural features. Compared with analyticalapproximations and theoretical predictions, the LSM numerical scheme shows generalapplicability for heterogeneous porous rocks.
Keywords: Elastic characteristics; lattice spring model (LSM); X-ray micro-computed tomography (XMCT); digital cores.